Associations between statin use and risk of non‐Hodgkin lymphomas by subtype. Issue 4 (30th March 2018) - Ye, Xibiao; Zhang, Geng; Righolt, Christiaan; Johnston, James B.; Banerji, Versha; Gibson, Spencer B.; Mahmud, Salaheddin M.
Abstract : Non‐Hodgkin lymphomas (NHL) are a group of cancers with highly heterogeneous biology and clinical features. Statins are increasingly prescribed to prevent cardiovascular diseases. Early evidence shows a preventive effect of statins for some cancers, but their effect on NHL risk is unclear. We conducted a population‐based nested case–control study involving 5, 541 NHL cases and 27, 315 controls matched for gender, age, place of residence and length of period of available prescription drug data. We assessed the use of statins prior to diagnosis (excluding the 12 months prior to the index date). We used conditional logistic regression models to estimate odds ratio (OR) and 95% confidence interval (CI) for use of any statin, adjusting for medical conditions, number of family physician visits for 5 years prior to index date, healthcare utilization, income and use of other medications. Over one‐quarter of cases and controls were prescribed statins. Ever‐use of any statin was associated with lower risk of Total NHL (OR = 0.82, 95% CI 0.76–0.89) and of certain subtypes including diffuse large B‐cell lymphomas (DLBCL, OR = 0.77, 95% CI 0.65–0.92), plasma cell neoplasms (PCN, OR = 0.76, 95% CI 0.63–0.91) and other B‐cell NHL (0.75, 0.59–0.95). Analysis by statin type suggested that the association was limited to high potency statin and lipophilic statin users. No clear duration or dose–response relationships were observed. Our findings provide evidence that statin use can reduce the risk of DLBCL and plasma cell lymphomas, but not other NHL types. Further studies are warranted to verify these associations and to examine the biological mechanisms. Abstract : What's new? In addition to lowering cholesterol, statins may reduce the risk of several cancers. The impact of these drugs on non‐Hodgkin lymphoma (NHL) has been unclear, however. In this study, the authors examined associations between different types of statins and various subtypes of NHL. They found that high‐potency and highly lipophilic statins were associated with reduced risk of diffuse large B‐cell lymphomas (DLBCL) and plasma cell lymphomas, but not other NHL types. Further studies are needed to verify these associations and to understand the underlying mechanisms.